2019
DOI: 10.1097/md.0000000000018355
|View full text |Cite
|
Sign up to set email alerts
|

Selection of patients with ovarian cancer who may show survival benefit from hyperthermic intraperitoneal chemotherapy

Abstract: Background: The use of hyperthermic intraperitoneal chemotherapy (HIPEC) after cytoreductive surgery has been extensively studied in patients with peritoneal carcinomatosis from various malignancies. However, the effectiveness of HIPEC for ovarian cancer is still controversial. Therefore, we performed this meta-analysis to identify patients with ovarian cancer who can obtain survival benefit from HIPEC. Methods: Articles regarding HIPEC in the MEDLINE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 35 publications
1
28
0
1
Order By: Relevance
“…The outcomes of the meta-analysis by Kim et al for patients with primary disease showed an improved diseasefree survival (DFS) in patients who received HIPEC as part of CRS (5 studies, 630 patients, HR: 0.580, 95% CI: 0.476-0.706) when compared to no-HIPEC. Improved survival remained after subgroup analysis of study design, stage and adjustment for potential confounders (age, stage, NACT, grade, ECOG status and histology) (9). Additionally, the HIPEC groups showed improved OS compared to controls (5 studies, 591 patients, HR: 0.611, 95% CI: 0.376-0.992).…”
Section: Hipec For Primary Eocmentioning
confidence: 90%
“…The outcomes of the meta-analysis by Kim et al for patients with primary disease showed an improved diseasefree survival (DFS) in patients who received HIPEC as part of CRS (5 studies, 630 patients, HR: 0.580, 95% CI: 0.476-0.706) when compared to no-HIPEC. Improved survival remained after subgroup analysis of study design, stage and adjustment for potential confounders (age, stage, NACT, grade, ECOG status and histology) (9). Additionally, the HIPEC groups showed improved OS compared to controls (5 studies, 591 patients, HR: 0.611, 95% CI: 0.376-0.992).…”
Section: Hipec For Primary Eocmentioning
confidence: 90%
“…No consensus exists for a specific chemotherapy agent or protocol to be used, and evidence is currently limited to single institution experiences and retrospective studies. Systematic reviews confirmed that only OS is improved in patients with recurrent disease [ 7 , 8 , 9 ], but subgroup analysis revealed that HIPEC also improved DFS in patients who received optimal cytoreduction [ 22 ]. Five-year DFS and OS rates were 18% and 32%, respectively, in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Five-year DFS and OS rates were 18% and 32%, respectively, in this series. HIPEC may overcome systemic resistance to platinum agents in this setting, but results are controversial and the question is open [ 22 , 25 , 29 , 30 ]. Prolonged NACT is believed to be a risk factor for platinum-resistance in selected histologic subtypes, which may give rise to a less sensitive recurrent disease [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…newly diagnosed or recurrent EOC) were different among the previous studies, which is also observed in ongoing clinical trials. 51 Thus, when, how, and on whom HIPEC should be carried out remains a significant issue.…”
Section: Role Of Hipec In Ovarian Cancermentioning
confidence: 99%